Assessing the prevalence of energy poverty and the impact thereof on educational well-being of high school students in Windhoek, Namibia - Seibes, Winniefred Angel (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPhil)--Stellenbosch University, 2023.